Hardware Choice and Risk Factors of Talonavicular Arthrodesis Non-Union. Issue 1 (January 2022) - Moncman, Tara; Corr, Daniel O.; Kothari, Parth; O'Neil, Joseph T.; Pedowitz, David I.
Category: Midfoot/Forefoot; Ankle Introduction/Purpose: Talonavicular arthrodesis is a commonly performed procedure in orthopedic foot and ankle surgery, for conditions including osteoarthritis, instability, and others. The surgery is frequently performed as part of a double or triple arthrodesis. Multiple surgical constructs have been described, including screws, plate/screw constructs, and staple/screw constructs. Few studies exist that specifically focus on the talonavicular joint, and those that do are often limited by low patient volumes. Studies that do examine non-union of the talonavicular joint do not offer comparative data on non-union rates between the different methods of fixation. The purpose of this study was to determine the rate of arthrodesis in talonavicular fusion surgery among different fixation techniques and determine if hardware has a significant effect on union rate among patient factors. Methods: This is a retrospective single institution, multi-surgeon study evaluating arthrodesis rates in the talonavicular joint. Adult patients undergoing primary talonavicular fusion (isolated or as part of double/triple arthrodesis) from 2015-2018 with a minimum of 3-month radiographic follow-up were studied. Patients undergoing revision talonavicular fusion or fusion as part of Charcot reconstruction were excluded. Patient radiographic and chart notes were reviewed to assess fixation type (single screw, 2-hole compression plate, or screw + staple), the status of the arthrodesis at >=3 months and any hardware complications or reoperations following the index procedure. Descriptive statistics were generated for standard patient demographics and co- morbidities. Non-union rates were calculated for the cohort as a whole and for each fixation technique utilized along with the frequency of hardware complications/removal. Univariate analysis was performed to determine risk factors for increased non- union rate, including patient demographics, co-morbidities, and fixation technique. Results: A total of 198 patients were included. Hardware included 131 double straight screws, 42 two-hole compression plates, and 25 screw + staple constructs. Seventeen patients (8.59%) had a nonunion of the talonavicular joint at >3 months, while 18 patients (9.09%) had hardware complications of breakage or prominence and 11 (5.56%) required eventual removal. Hardware type was not a significant predictor of nonunion, as 11 patients had straight screw hardware (8.40%), while 3 had a two-hole plate (7.14%) and 3 had screw + staple (12%) (p=0.801). Hardware breakage or backing out occurred in 6/131 patients with straight screws (4.58%), 5/42 with 2-hole plates (11.90%), and 7/25 with staple + screw (28%) (p=0.001). Hardware removal was necessary in 5 (3.82%) straight screw patients, 3 (7.14%) two-hole plate patients, and 3 (12%) screw + staple patients (p=0.186). Patient age, sex, diabetic and smoking status were not significant for nonunion or hardware complication. Conclusion: The type of hardware used in talonavicular arthrodesis is not a significant factor in achieving union. Staple + screw constructs may be more susceptible to hardware breakage or migration, but was not significant for the necessity of hardware removal, as a number of patients remain painless and achieve the intended union. The authors recommend that physicians can make decisions of which to utilize based on familiarity and preference. Further study is indicated on even larger patient cohorts with increased population of nonunion cases so that further significant patient risk factors for nonunion of the joint can be identified.